(3JJeje GdahGFO hJHjjf GdebGUOs - (3GdLGeYj, GdYGedj, GdMGQKj GdgePGfj, fhQ GdOjf, Ydj Hf GdMSjf Hf eMjj GdOjf GHf YHO GddWja Hf Ydj, J (B1135(3g`s ((3LhGO Hf eMjj GdOjf GdYGedjs)
(3ChdgG (B:s
(3aj GdJUOjb HJhMjOc TQM GdUOhQ haj GdKfGA(B... (3JYdjb eJcad HEjVGM GdeYGfj hJTjjjO GdeHGfj(B...s
(3BNQgG (B:s
(3hCeG GdJMOjO aTCfg Cf jPcQ aj eHGMK (B... (3GdJj gj ef GdebGUO GdeJYdbI HGcJSGH GdJUhQGJ(B... (3adfNJe fMf GdcdGe MGeOjf ddg Gdedc(B...s
(3JHUQI GdYfhGf (B:s
(3TQM MGTjI GdedG fLe GdOjf Hf TgGH GdOjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B4(3, U(B281s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdadSaI hGdefWbs